THE CONCEPT AND VALUES OF CHARACTER EDUCATION ON AL-QUR’AN: A CRITICAL STUDY OF SURAH AL-BAQARAH VERSE 261-267 - Harmoko Harmoko (Universitas Islam Negeri Alauddin Makassar, 2022)
This study discusses the Concepts and Values of Character Education in the Qur'an Surah al-Baqarah: 261-267. This research uses the library research method, namely by collecting data or materials related to the theme of the discussion and the problems, which are taken from library sources. The research results show that in QS. al-Baqarah: 261-267 there are values of character education namely: religious, social care, and friendly/communicative. These three characters reflect religious teachings that emphasize hablum minallah and hablun minnannas.